2021
DOI: 10.1093/ndt/gfab188
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C kidney functional reserve: a simple method to predict outcome in chronic kidney disease

Abstract: Background Kidney Functional Reserve (KFR), the only clinical kidney stress test, is not routinely measured because complexity of measurement has limited clinical application. We investigated the utility of plasma cystatin C (CysC) after oral protein loading to determine KFR in stage 3 and 4 CKD. Methods Following a 24 hour low protein diet, KFR was measured after oral protein by hourly plasma CysC and compared with simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Hourly urine collection without an indwelling bladder catheter may be inaccurate, and selection of the baseline GFR as the lower of the two CrCl before stimulation, and the peak GFR as the highest CrCl within 3 h post stimulation, needs further validation [5]. Replacement of creatinine with the more accurate filtration marker cystatin C did show conflicting results, questioning whether changes in plasma levels of creatinine and cystatin C reflect the stimulation-induced filtration dynamics fast enough to be detected within an hour [35,38]. More work is therefore required to standardize stimulation and GFR and to optimize the detection of dynamic changes in GFR to improve robustness of RFR measurement.…”
Section: Challenges With Measurement Of Renal Functional Reservementioning
confidence: 99%
“…Hourly urine collection without an indwelling bladder catheter may be inaccurate, and selection of the baseline GFR as the lower of the two CrCl before stimulation, and the peak GFR as the highest CrCl within 3 h post stimulation, needs further validation [5]. Replacement of creatinine with the more accurate filtration marker cystatin C did show conflicting results, questioning whether changes in plasma levels of creatinine and cystatin C reflect the stimulation-induced filtration dynamics fast enough to be detected within an hour [35,38]. More work is therefore required to standardize stimulation and GFR and to optimize the detection of dynamic changes in GFR to improve robustness of RFR measurement.…”
Section: Challenges With Measurement Of Renal Functional Reservementioning
confidence: 99%
“…Ingestion of meat increases GFR in the healthy kidney, and a protein load is one way of determining kidney functional reserve, that is renal reserve [ 28 ]. Although the kidney functional reserve has been shown to be useful in the clinical assessment of the severity of kidney disorders [ 29 ], it has not been extensively used because of the requirement to measure GFR by invasive methods after a protein load [ 30 ]. Cooked meat does not contain any undenatured cystatin C, and the increase in kidney function after such a meal is reflected in the cystatin C level, which will be reduced.…”
Section: Non‐renal Factors Influencing the Levels Of Creatinine Or Cy...mentioning
confidence: 99%
“…Cooked meat does not contain any undenatured cystatin C, and the increase in kidney function after such a meal is reflected in the cystatin C level, which will be reduced. This observation has been used to devise a simple way of estimating kidney functional reserve by measuring this reduction in the cystatin C level after a protein load [ 30 , 31 ].…”
Section: Non‐renal Factors Influencing the Levels Of Creatinine Or Cy...mentioning
confidence: 99%
“…Recent studies in cardiothoracic surgery demonstrated that among patients with a normal sCr those with low KFR (<15 ml/min) were at higher risk of development of postoperative AKI 94 and that the AKI episode itself reduced postoperative KFR 95 . Thus, reduced KFR highlights a potential vicious cycle of AKI risk followed by CKD, which itself increases further risk of AKI that will further reduce KFR 96 . There are few clinical studies of KFR, since testing usually involves hourly creatinine clearance measurements, which is cumbersome in non‐catheterised patients.…”
Section: Some Things Last Forever – the Consequences Of Akimentioning
confidence: 99%
“… 95 Thus, reduced KFR highlights a potential vicious cycle of AKI risk followed by CKD, which itself increases further risk of AKI that will further reduce KFR. 96 There are few clinical studies of KFR, since testing usually involves hourly creatinine clearance measurements, which is cumbersome in non‐catheterised patients. However, serial serum cystatin C measurements before and after a liquid protein meal has simplified KFR measurement in healthy and CKD subjects 96 , 97 and should allow easier detection of subclinical CKD in clinical settings associated with high AKI risk.…”
Section: Some Things Last Forever – the Consequences Of Akimentioning
confidence: 99%